Digital Transformation and Competitive Strategies of Nutmeg-Processing MSMEs: A SWOT–QSPM Analysis - Marlinda Apriyani; Teguh Budi Trisnanto; Dian Nirmala Dewi (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study identifies key factors affecting the marketing competitiveness of nutmeg-processing MSMEs in Tanggamus Regency and formulates prioritized strategies using an extended SWOT–QSPM framework incorporating digital and institutional perspectives. Methodology: A descriptive quantitative approach was used, with data from semi-structured interviews with nine purposively selected experts in two nutmeg-producing sub-districts. IFAS–EFAS, SWOT, and QSPM were applied to determine and prioritize the strategies. Results: The IFAS (3.76) and EFAS (3.14) scores indicate a strong strategic position. Strengths in product quality, customer relationships, and skilled labor are constrained by limited capital, weak financial management, and a narrow marketing reach, whereas government support, digital expansion, and rising demand present key opportunities. The QSPM ranks digital market development (TAS = 13.64), product quality and innovation (TAS = 12.76), and distribution network expansion (TAS = 11.82) as priority strategies. Conclusions: Nutmeg-processing MSMEs can enhance their competitiveness by aligning their internal strengths with digital and institutional opportunities. Digital capability is a key driver, supported by strategies for digital adoption, innovation, collaboration, and managerial capacity building. Limitations: Limited to two sub-districts and subjective QSPM scoring, these findings lack generalizability. Future research should expand the sample size and utilize Fuzzy-AHP to enhance validity. Contributions: This study proposes a quantitative model that integrates strategy, digital transformation, and ecosystems, identifying digital expansion as a critical capability for rural MSMEs in agro-processing.